Systematic Review of Educational Level and Evaluation Tools for Computational Thinking Skill - Rahim, Fanny Rahmatina; Widodo, Ari; Suhandi, Andi; Ha, Minsu (Postgraduate, University of Mataram, 2024)
The primary aim of this research was to conduct a systematic review on the assessment of computational thinking skills. The employed research method involved a thorough exploration of diverse databases through Google Scholar, employing the keyword